Assessing functional status and the survival benefit of chemotherapy for advanced non-small cell lung cancer using administrative claims data. Issue 1 (January 2015) - Feliciano, Josephine; Gardner, Lisa; Hendrick, Franklin; Edelman, Martin J.; Davidoff, Amy
Highlights Disability status can serve as a proxy for performance status in secondary analyses. Chemotherapy had a strong protective effect for good DS patients. Poor DS patients benefit from chemotherapy to a lesser degree than good DS patients.